Pseudoangiomatous Stromal Hyperplasia in an Unmarried Female with Asymmetric Breasts (GAIMS Journal of Medical Sciences, 2025)
Pseudoangiomatous stromal hyperplasia (PASH) is a non-cancerous mesenchymal growth in the breast. It was first described by Vuitch, et al. in 1986 wherein it appeared as a palpable breast lump in a patient. Only around 109 cases had been documented by 2008. The etiology and pathogenesis of PASH are still unknown; however, there is some evidence suggesting PASH is hormone dependent. Herewith we present a case of 29 years old unmarried lady who presented to plastic surgery department of our hospital with complaint of painless, asymmetric breasts. Her mammography showed global dense asymmetrical breast parenchyma more in left breast compared to her right breast. Her PASH diagnosis was confirmed on gold standard test of histopathology.